DIE KAPELAAN: IN DIENS MET DIE SWAARD VAN DIE HEILIGE GEES - Afdeling Godsdienstige Publikasies, Kapelaan-generaal (Scientia Militaria - South African Journal of Military Studies, 2012)
The short article below deals with the role of the Chaplain throughout the history of South Africa and with the South African Chaplain Services in particular.